Improved surface of additive manufactured products by coating. (October 2016) - Yao, Shan; Wang, Tingli
Abstract: The additive manufactured coated sand products had obvious staircases on the surface and lots of small holes inside. The alcohol based refractory coating and the water based refractory coating were applied to improve the surface of the samples. The polygonal samples were used to check the effects of the coatings on reducing the surface roughness. The "8" shape samples were used to compare the effect of dipping time on the moisture content and the tensile strength of samples and the coating thickness. Results showed that the surface of samples could be improved by both alcohol based refractory and water based refractory coating. By the alcohol based refractory coating, the moisture content and the coating thickness increased and the tensile strength decreased with the dipping time obviously. By the water based refractory coating, the moisture content, the tensile strength of samples and the coating thickness kept approximately changeless with the increment of dipping time, which meant it could have enough time to dip to assure the coating's quality on the surface of the samples. In conclusion, it was suitable to apply water based refractory coating and the dipping process to improve the surface of additive manufactured coated sand products.